1985
DOI: 10.1523/jneurosci.05-05-01208.1985
|View full text |Cite
|
Sign up to set email alerts
|

Selective reinnervation of intercostal muscles transplanted from different segmental levels to a common site

Abstract: We transplanted external intercostal muscles from one of several thoracic (T) levels to the neck of adult rats. The cervical sympathetic trunk, which innervates the superior cervical ganglion, was cut, and its proximal end was apposed to the muscle. Preganglionic axons in the trunk reinnervated muscle fibers in the transplants. We determined the segmental origin of synaptic inputs to transplanted muscles by recording intracellularly from muscle fibers while stimulating individual ventral roots which supply axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 37 publications
1
42
3
Order By: Relevance
“…This interpretation is at least philosophically similar to that of the segmental identity of intercostal muscles, forelimb muscles, and the diaphragm proposed by Sanes and his co-workers (e.g., Wigston and Sanes, 1985;Wigston, 1986;Laskowski and Sanes, 1987;DeSantis et al, 1992). Both during development and during reinnervation, muscle fibers in different regions within these muscles receive selective innervation from motoneurons in different segmental regions of the spinal cord.…”
Section: Compartmental Identity Of Adult Musclessupporting
confidence: 79%
“…This interpretation is at least philosophically similar to that of the segmental identity of intercostal muscles, forelimb muscles, and the diaphragm proposed by Sanes and his co-workers (e.g., Wigston and Sanes, 1985;Wigston, 1986;Laskowski and Sanes, 1987;DeSantis et al, 1992). Both during development and during reinnervation, muscle fibers in different regions within these muscles receive selective innervation from motoneurons in different segmental regions of the spinal cord.…”
Section: Compartmental Identity Of Adult Musclessupporting
confidence: 79%
“…Regenerating preganglionic axons in the mammalian autonomic nervous system exhibit segmental selectivity during reinnervation of superior cervical ganglion neurons (Langley, 1897;Nja and Purves, 1977). Furthermore, when preganglionic axons are forced to grow into transplanted intercostal muscles, they innervate those inappropriate targets in a manner that is segmentally specific (Wigston and Sanes, 1985). We found that motor axons from spinal segment 8 reformed an apparently normal hindlimb innervation pattern even when transected near the plexus.…”
Section: Discussionmentioning
confidence: 79%
“…If regenerating axons are able to grow freely only in close proximity to their target muscles, the relatively large distances separating muscles in limbs of mature animals may make it impossible for the axons to express any intermuscular selectivity they may possess Wigston and Sanes, 1985). Hence, we cannot rule out the possibility that these regenerating axons could distinguish appropriate from inappropriate targets if given unimpeded access to both at close range.…”
Section: Discussionmentioning
confidence: 99%
“…In a few examples this appears to involve a degree of selective reinnervation of the post-synaptic targets. Examples include reinnervation of the neuromuscular junction of fish, amphibia, and mammals (Sperry & Arora, 1965 (however, see Scherer, 1986); Dennis & Yip, 1978;Wigston & Sanes, 1985), regeneration of sensory input onto spinal motor neurones in the bull-frog (Sah & Frank, 1984), reinnervation of autonomic ganglia in mammals (NjA, & Purves, 1977;Purves, Thompson & Yip, 1981), and the restoration of correct retinotectal projections in fish and amphibia (Attardi & Sperry, 1963;Fujisawa, 1981). Specificity has been suggested by some observations on synaptic regeneration of identified invertebrate neurones, both in vivo (Jansen & Nicholls, 1972) and in vitro (Fuchs, Nicholls & Ready, 1981).…”
Section: Introductionmentioning
confidence: 99%